The gift of failure : how the best parents learn to let go so their children can succeed - Lahey, Jessica (Harper, an imprint of HarperCollinsPublishers, 2015)
Counsels parents of school-aged children on how to overcome tendencies toward overprotectiveness to allow children to develop independence. --Publisher's description.